The Effect of Training and Incentives on Work Motivation Which Implicates Employee Performances in the Regional Disaster Management Agency Office Merangin Regency - Pantun Bukit; Osrita Hapsara; Jondri Jondri (Greenation International Journal of Economics and Accounting, 2023)
The purpose of this study is to obtain an overview of training, incentives, work motivation, and employee performance at the Regional Disaster Management Agency Office of the Merangin Regency. To find out the direct and indirect effects of training and incentives on employee motivation at the Regional Disaster Management Agency Office of Merangin Regency. To determine the effect of work motivation on employee performance at the Regional Disaster Management Agency Office of Merangin Regency. To determine the effect of training and incentives through work motivation on employee performance. The type of data obtained in this study were quantitative data sourced from primary data by conducting research and questionnaires, secondary data were obtained by reading, studying, and understanding literature and library books or data from agencies related to the research. In this study, the object of the research was employees at the Regional Disaster Management Agency Office in Merangin Regency. Training and incentives simultaneously affect the motivation of employees of the Regency Regional Disaster Management Agency. Partial training has a positive and significant effect on motivation. Incentives partially have a negative and significant impact on motivation. Training and incentives simultaneously have a significant effect on the performance of employees of the Regency Regional Disaster Management Agency. Partial training has a significant effect on performance. While incentives partially have no significant effect on performance. Motivation partially has a significant effect on performance. Training and incentives together have a significant effect on motivation (Y) and performance.